The Control of an Upper-Limb CC by Means of a Particle Swarm Optimized Active Force Control for Motor Recovery - Zahari, Taha; Anwar, P. P. Abdul Majeed; Ismail, Mohd Khairuddin; M. Y., Wong; M. A., Abdullah; M. A., Mohd Razman (Springer, 2017)
The modelling and control of a two degree of freedom upper extremity exoskeleton for motor recovery is presented in this paper. The dynamic modelling of the upper arm and the forearm for both the anthropometric based human upper limb as well as the exoskeleton was attained via the Euler-Lagrange formulation.